ANALISIS PENGARUH KUALITAS PRODUK, HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK PULL&BEAR DI GRAND INDONESIA, JAKARTA - Anggara Tritama, (2021)
This research is a quanitative study which aims to determine the efect of product quality, price and brand image on purchasing decision. The population in this study are consumers who have purchased Pull & Bear products in Grand Indonesia, Jakarta. The number of samples taken was 75 respondents, with a probability sampling method with a purposive sampling method. Data collection was carried out through distributing google form questionaires. The analysis technique used is the PLS (Partial Least Square) analysis method with the SmartPLS 3.0 software. The results of this study indicate that (1) the product quality variable has a significant effect on purchasing decisions. (2) the price variable has a significant effect on purchasing decisions. (3) the brand image variable has no significant effect on purchasing decisions.